Why does one choose to be homeless in Singapore? - Cheng, Hui Jie (2018)
As a country that prides itself as “a nation of homeowners” with an overall home ownership rate of 90.9% in 2016, it is tough to fathom that there are homeless people in Singapore. Yet, there are 300 cases of homelessness recorded last year. Why do individuals choose to sleep rough despite owning houses? There are no existing studies on homeless individuals in Singapore. Using in-depth interviews with three homeless individuals, two volunteers and two welfare organizations, this research aims to find out: Why does one choose to be homeless in Singapore today? Findings suggest that homelessness is hardly a rational nor a deviant choice of individuals in Singapore. Homelessness is a constrained choice for them. Recommendations were made to prevent, alleviate, accept, and raise awareness about homelessness in Singapore. This study aims to spark future research efforts.